2004
DOI: 10.1111/j.1460-9568.2004.03706.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic interleukin‐6 exposure alters metabotropic glutamate receptor‐activated calcium signalling in cerebellar Purkinje neurons

Abstract: Chronic central nervous system expression of the cytokine interleukin-6 (IL-6) is thought to contribute to the histopathological, pathophysiological, and cognitive deficits associated with various neurological disorders. However, the effects of chronic IL-6 expression on neuronal function are largely unknown. Previous studies have shown that chronic IL-6 exposure alters intrinsic electrophysiological properties and intracellular Ca2+ signalling evoked by ionotropic glutamate receptor activation in cerebellar P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 70 publications
2
27
0
Order By: Relevance
“…This might be different when IL-6 is chronically elevated. Increased neuronal death has been described after chronic treatment with IL-6 in vitro and animals with chronic IL-6 expression in astrocytes show enhanced neurodegeneration and increased sensitivity to kainite-induced seizures (Qiu et al, 1998;Nelson et al, 2004;Conroy et al, 2004;Campbell et al, 1993;Samland et al, 2003). It is not yet clear whether adenosine A 1 receptor expression is affected by chronic elevated IL-6 levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be different when IL-6 is chronically elevated. Increased neuronal death has been described after chronic treatment with IL-6 in vitro and animals with chronic IL-6 expression in astrocytes show enhanced neurodegeneration and increased sensitivity to kainite-induced seizures (Qiu et al, 1998;Nelson et al, 2004;Conroy et al, 2004;Campbell et al, 1993;Samland et al, 2003). It is not yet clear whether adenosine A 1 receptor expression is affected by chronic elevated IL-6 levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of IL-6 in that phenomenon has been regarded as a doubleedged sword, since both neuroprotective and detrimental properties were associated to its expression. On one hand it has been shown that IL-6 protects cultured neurons (Carlson et al, 1999;Ali et al, 2000;Pizzi et al, 2004) and is beneficial in several models of neurodegenerative diseases (Bensadoun et al, 2001;Bolin et al, 2002;Penkowa et al, 2001;Loddick et al, 1998;Ali et al, 2000, Swartz et al, 2001Herrmann et al, 2003); on the other hand, chronic treatment of cultured neurons with IL-6 or chronic expression of IL-6 in astrocytes might result in neuronal death and neurodegeneration (Qiu et al, 1998;Nelson et al, 2004;Conroy et al, 2004;Campbell et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Such a store might release [Ca 2ϩ ] i via a IP 3 -mediated mechanism or via Ca 2ϩ -induced Ca 2ϩ release (CICR). Metabotropic glutamate receptor-mediated delayed Ca 2ϩ release is essential in PC dendrites and spines (Finch and Augustine, 1998;Takechi et al, 1998), but its putative role in shaping somatic Ca 2ϩ transients is less clear and may be of importance mainly during postnatal PC development (Liljelund et al, 2000;Nelson et al, 2004). We hypothesize that ER-mediated Ca 2ϩ oscillations (waves) are decreasing in parallel to the increase in PV expression also based on results that in oocytes, PV prevents the generation of IP 3 -induced Ca 2ϩ waves and restricts Ca 2ϩ signals to local Ca 2ϩ release sites (Dargan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The selective in vivo deletion of the neuropoietic cytokine receptor subunit gp130 in noradrenergic neurons results in a decrease in the number of cholinergic neurons innervating the sweat glands, although the total number of innervating neurons is unchanged (Stanke et al 2006). Additional studies of hippocampal neurons show that elevated levels of IL-6 both in vivo and in vitro modulate the expression of L-type calcium channels and alter the dynamics of calcium signaling and network activity (Nelson et al 2004;Vereyken et al 2007). These results indicate that signaling through the IL-6 receptor gp130 may regulate neurotransmitter phenotype by modulating calcium signaling.…”
Section: Calcium Signaling In Neuronal Developmentmentioning
confidence: 99%